Powerful teacher education : lessons from exemplary programs - Darling-Hammond, Linda (San Francisco, CA : Jossey-Bass, 2006)
Powerful Teacher Education describes the strategies, goals, content, and processes of seven highly successful and long-standing teacher education programs - Alverno College, Bank Street College, Trinity University, University of California, Berkeley, University of Southern Maine, University of Virginia, and Wheelock College.
Includes bibliographical references
Keywords: Teachers -- Training of -- United States